2019
DOI: 10.1016/j.jcte.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid vascularization is an important ultrasonographic parameter in untreated Graves’ disease patients

Abstract: Graves’ disease is characterized by two sonographic features, hypoechogenicity and increased blood flow. The aim of this study was to review retrospectively ultrasound features and biochemical data of a cohort of untreated Graves’ disease patients. We reviewed charts of 42 such patients, who were referred to our Endocrinology Unit from January 2013 to May 2018. One operator performed all the thyroid sonographic scans. Serum TSH, FT3, FT4 and TSH-receptor antibodies (TRAb) levels at the time of ultrasound exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 32 publications
(58 reference statements)
1
28
0
2
Order By: Relevance
“…The new data regarding the influence of SAT-risk HLA alleles on the clinical course of the disease may facilitate diagnosis and treatment. In some patients, the SAT US image may be challenging to evaluate, as-for example-the typical US pattern and vascularization in SAT is sometimes similar to that of the early phase of chronic autoimmune thyroiditis [29]. In HLA-B*18:01 carriers, the SAT US pattern may be highly misleading, largely resembling a large thyroid tumor [27].…”
Section: Discussionmentioning
confidence: 99%
“…The new data regarding the influence of SAT-risk HLA alleles on the clinical course of the disease may facilitate diagnosis and treatment. In some patients, the SAT US image may be challenging to evaluate, as-for example-the typical US pattern and vascularization in SAT is sometimes similar to that of the early phase of chronic autoimmune thyroiditis [29]. In HLA-B*18:01 carriers, the SAT US pattern may be highly misleading, largely resembling a large thyroid tumor [27].…”
Section: Discussionmentioning
confidence: 99%
“…After the application of antithyroid drugs (ATDs), the abnormal elevation of TRAbs can be used to predict GD recurrence risk [ 43 ]. TRAbs correlates positively also with thyroid vascularization at color-flow doppler and the odds of hyperthyroidism recurrence [ 44 ]. It has been reported that in GD patients developing hypothyroidism, TSAbs increase significantly 6 months after radioiodine treatment.…”
Section: Clinical Significance Of Trabs Tpoabs and Tgabsmentioning
confidence: 99%
“…Differentiation of destruction-induced thyrotoxicosis (painless or subacute thyroiditis) from GD is important for the selection of the correct therapy. GD but not SAT can be triggered by stressful events (8,9) and albeit hypoechogenicity can be present in both, even though in GD the thyroid is diffusely hypoechoic, hypervascularization is generally not present in patients with SAT (10,11). It is, however, often difficult to make this distinction without measurement of RAIU.…”
Section: Introductionmentioning
confidence: 99%